A dinosaur ate my homework - Nelson, Ray, 1965-; Kelly, Douglas, 1955-; Adams, Ben. (Hillsboro, Or. : Beyond Words Pub., 1996)
Facts about different kinds of dinosaurs accompany a story about a boy who brings various prehistoric animals to school for show-and-tell.
"With the cooperation of Raymond T. Rye, National Museum of Natural History, Smithsonian Insitution."
Keywords: Dinosaurs -- Fiction; Schools -- Fiction; Stories in rhyme